GMAT Question of the Day - Daily to your Mailbox; hard ones only

It is currently 16 Oct 2019, 05:52

Close

GMAT Club Daily Prep

Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized
for You

we will pick new questions that match your level based on your Timer History

Track
Your Progress

every week, we’ll send you an estimated GMAT score based on your performance

Practice
Pays

we will pick new questions that match your level based on your Timer History

Not interested in getting valuable practice questions and articles delivered to your email? No problem, unsubscribe here.

Close

Request Expert Reply

Confirm Cancel

If f(x) = 5x^2 - 4 and g(x) = 3x + 1, then what is the sum

  new topic post reply Question banks Downloads My Bookmarks Reviews Important topics  
Author Message
TAGS:

Hide Tags

Find Similar Topics 
Math Expert
User avatar
V
Joined: 02 Sep 2009
Posts: 58384
If f(x) = 5x^2 - 4 and g(x) = 3x + 1, then what is the sum  [#permalink]

Show Tags

New post 09 Jul 2014, 06:06
6
29
00:00
A
B
C
D
E

Difficulty:

  65% (hard)

Question Stats:

65% (02:37) correct 35% (02:48) wrong based on 409 sessions

HideShow timer Statistics

Most Helpful Expert Reply
Math Expert
User avatar
V
Joined: 02 Sep 2009
Posts: 58384
Re: If f(x) = 5x^2 - 4 and g(x) = 3x + 1, then what is the sum  [#permalink]

Show Tags

New post 09 Jul 2014, 06:06
7
12
SOLUTION

If \(f(x) = 5x^2 - 4\) and \(g(x) = 3x + 1\), then what is the sum of all the values of \(m\) for which \(f(m - 1) = g(m^2 + 1)\) ?

A. -10
B. -5
C. 0
D. 5
E. 10

\(f(x) = 5x^2 - 4\), then \(f(m - 1)=5(m-1)^2 - 4=5m^2-10 m+1\);
\(g(x) = 3x + 1\), then \(g(m^2 + 1)=3(m^2 + 1) + 1=3m^2+4\).

Since given that \(f(m - 1) = g(m^2 + 1)\), then \(5m^2-10 m+1=3m^2+4\) --> \(2m^2-10m-3=0\).

Next, Viete's theorem states that for the roots \(x_1\) and \(x_2\) of a quadratic equation \(ax^2+bx+c=0\):

\(x_1+x_2=\frac{-b}{a}\) AND \(x_1*x_2=\frac{c}{a}\).


Thus according to the above \(m_1+m_2=\frac{-(-10)}{2}=5\).

Answer: D.

Try NEW Algebra DS question.
_________________
General Discussion
Intern
Intern
User avatar
S
Joined: 24 Apr 2013
Posts: 15
Location: Russian Federation
GMAT ToolKit User
Re: If f(x) = 5x^2 - 4 and g(x) = 3x + 1, then what is the sum  [#permalink]

Show Tags

New post 09 Jul 2014, 08:46
2
F(x)=5x^2-4
F(m-1)=5(m-1)^2-4
5(m^2-2m+1)-4
5m^2-10m+5-4
5m^2-10m+1

G(x)=3x+1
G(m^2+1)=3(m^2+1)+1
3m^2+3+1
3m^2+4

5m^2-10m+1=3m^2+4
2m^2-10m-3=0

D=b^2-4ac
D=100-4(-6)=100+24=124

x(1) = 10+2(root)31/4
x(2) = 10-2(root)31/4

10+2(root)31/4 + 10-2(root)31/4 = 20/4 = 5

Answer is D
Intern
Intern
avatar
Joined: 19 Nov 2013
Posts: 24
Location: India
Concentration: Strategy, Technology
WE: Information Technology (Computer Software)
Re: If f(x) = 5x^2 - 4 and g(x) = 3x + 1, then what is the sum  [#permalink]

Show Tags

New post 09 Jul 2014, 08:53
1
The ans is 5

putting the values gives us 2m^2-10m-3=0

solving this gives us m= (10+sqrt(124))/4 and (10-sqrt(124))/4

21/4-1/4 =5 ans
Senior Manager
Senior Manager
User avatar
Joined: 13 Jun 2013
Posts: 266
Re: If f(x) = 5x^2 - 4 and g(x) = 3x + 1, then what is the sum  [#permalink]

Show Tags

New post 09 Jul 2014, 10:19
3
Bunuel wrote:


If \(f(x) = 5x^2 - 4\)and \(g(x) = 3x + 1\), then what is the sum of all the values of \(m\) for which \(f(m - 1) = g(m^2 + 1)\) ?

A. -10
B. -5
C. 0
D. 5
E. 10

Kudos for a correct solution.



f(m-1)= 5(m-1)^2 -4
= 5(m^2+1-2m) -4
=5m^2+5-10m-4
= 5m^2-10m +1

g(m^2+1)= 3(m^2+1) +1
=3m^2+4

now f(m-1)=g(m^2+1)
5m^2-10m +1 = 3m^2+4
2m^2-10m -3=0

also, any quadratic equation can be written as
x^2-(sum of the roots)x + product of the roots

here since coeff. of m^2 is 2, therefore we will divide the whole expression by 2
and we will get, m^2-5m-3/2=0

thus sum of roots = 5

hence D
Intern
Intern
avatar
Joined: 29 Oct 2013
Posts: 18
Re: If f(x) = 5x^2 - 4 and g(x) = 3x + 1, then what is the sum  [#permalink]

Show Tags

New post 09 Jul 2014, 12:11
1
Substituting (m-1) and (m^2+1) in place of x in the functions f(x) and g(x) respectively,

5(m-1)^2-4=3(m^2+1)
5m^2-10m+5-4=3m^2+3+1
2m^2-10m=0
2m(m-5)=0

2m=0 and m-5=0

The roots of m are 0 and 5 and their sum is 5

Answer D
Intern
Intern
User avatar
Joined: 23 May 2014
Posts: 8
Re: If f(x) = 5x^2 - 4 and g(x) = 3x + 1, then what is the sum  [#permalink]

Show Tags

New post 09 Jul 2014, 18:33
1
Subbing (m-1) into f(x) yields 5m^2 - 10m + 1

Subbing (m^2 + 1) into g(x) yields 3m^2 + 4

Setting f(m-1) equal to g(m^2 + 1) yields
3m^2 + 1 = 5m^2 - 10m + 1

This simplifies to
0 = 2m^2 - 10m - 3

Using Viete's rules, we know that the sum of the roots x1 and x2 in ax^2 + bx + c is equal to -b/a, hence
x1 + x2 = -(-10)/2 = 5

This is the desired answer. Therefore, D.
SVP
SVP
User avatar
Status: The Best Or Nothing
Joined: 27 Dec 2012
Posts: 1749
Location: India
Concentration: General Management, Technology
WE: Information Technology (Computer Software)
Re: If f(x) = 5x^2 - 4 and g(x) = 3x + 1, then what is the sum  [#permalink]

Show Tags

New post 09 Jul 2014, 22:42
2
\(f(x) = 5x^2 - 4\)

\(f(m-1) = 5 (m-1)^2 - 4\)

\(= 5(m^2 - 2m + 1) - 4\)

\(= 5m^2 - 10m + 5 - 4\)

\(= 5m^2 - 10m + 1\) .............. (1)

g(x) = 3x+1

\(g(m^2 + 1) = 3(m^2 + 1) + 1\)

\(= 3m^2 + 4\) ............ (2)

Equating (1) & (2)

\(5m^2 - 10m + 1 = 3m^2 + 4\)

\(2m^2 - 10m - 3 = 0\)

Sum of roots \(= \frac{-(-10)}{2} = 5\)

Answer = D
_________________
Kindly press "+1 Kudos" to appreciate :)
SVP
SVP
User avatar
Status: The Best Or Nothing
Joined: 27 Dec 2012
Posts: 1749
Location: India
Concentration: General Management, Technology
WE: Information Technology (Computer Software)
Re: If f(x) = 5x^2 - 4 and g(x) = 3x + 1, then what is the sum  [#permalink]

Show Tags

New post 09 Jul 2014, 22:46
1
fra wrote:
Substituting (m-1) and (m^2+1) in place of x in the functions f(x) and g(x) respectively,

5(m-1)^2-4=3(m^2+1)
5m^2-10m+5-4=3m^2+3+1
2m^2-10m=0
2m(m-5)=0

2m=0 and m-5=0

The roots of m are 0 and 5 and their sum is 5

Answer D


Equation would come up as \(2m^2 - 10m - 3\)

Answer = D, however individual roots cannot be 0 & 5
_________________
Kindly press "+1 Kudos" to appreciate :)
Intern
Intern
avatar
Joined: 29 Oct 2013
Posts: 18
Re: If f(x) = 5x^2 - 4 and g(x) = 3x + 1, then what is the sum  [#permalink]

Show Tags

New post 10 Jul 2014, 00:37
Thanks for pointing that out!
Math Expert
User avatar
V
Joined: 02 Sep 2009
Posts: 58384
Re: If f(x) = 5x^2 - 4 and g(x) = 3x + 1, then what is the sum  [#permalink]

Show Tags

New post 15 Jul 2014, 10:31
SOLUTION

If \(f(x) = 5x^2 - 4\) and \(g(x) = 3x + 1\), then what is the sum of all the values of \(m\) for which \(f(m - 1) = g(m^2 + 1)\) ?

A. -10
B. -5
C. 0
D. 5
E. 10

\(f(x) = 5x^2 - 4\), then \(f(m - 1)=5(m-1)^2 - 4=5m^2-10 m+1\);
\(g(x) = 3x + 1\), then \(g(m^2 + 1)=3(m^2 + 1) + 1=3m^2+4\).

Since given that \(f(m - 1) = g(m^2 + 1)\), then \(5m^2-10 m+1=3m^2+4\) --> \(2m^2-10m-3=0\).

Next, Viete's theorem states that for the roots \(x_1\) and \(x_2\) of a quadratic equation \(ax^2+bx+c=0\):

\(x_1+x_2=\frac{-b}{a}\) AND \(x_1*x_2=\frac{c}{a}\).


Thus according to the above \(m_1+m_2=\frac{-(-10)}{2}=5\).

Answer: D.

Kudos points given to correct solutions.

Try NEW Algebra DS question.
_________________
Manager
Manager
User avatar
Joined: 29 Mar 2015
Posts: 74
Concentration: Strategy, Operations
GMAT 1: 700 Q51 V33
WE: Research (Other)
GMAT ToolKit User Reviews Badge
Re: If f(x) = 5x^2 - 4 and g(x) = 3x + 1, then what is the sum  [#permalink]

Show Tags

New post 17 Apr 2015, 05:21
If \(f(x) = 5x^2 - 4\) and \(g(x) = 3x + 1\), then what is the sum of all the values of \(m\) for which \(f(m - 1) = g(m^2 + 1)\) ?

A. -10
B. -5
C. 0
D. 5
E. 10

Kudos for a correct solution.

[/quote]

f(m-1) = g(m^2+1)
5(m-1)^2-4=3(m^2+1)+1
2m^2 - 10m - 3 = 0
Sum of roots is = -b/a
so 10/2 = 5
_________________
If you like my post, Pl. do not hesitate to press kudos!!!!

Q51 on GMAT - PM me if you need any help with GMAT QUANTS!!!
Intern
Intern
avatar
Joined: 10 May 2016
Posts: 7
Re: If f(x) = 5x^2 - 4 and g(x) = 3x + 1, then what is the sum  [#permalink]

Show Tags

New post 11 May 2016, 02:47
f(m-1) = g(m^2+1)
5(m-1)^2-4=3(m^2+1)+1
2m^2 - 10m - 3 = 0
For equation aX^2+bX+C=0 sum of roots =(-b/a)

so here sum of roots= -(-10/2) = 5
CEO
CEO
User avatar
D
Status: GMATINSIGHT Tutor
Joined: 08 Jul 2010
Posts: 2977
Location: India
GMAT: INSIGHT
Schools: Darden '21
WE: Education (Education)
Reviews Badge
Re: If f(x) = 5x^2 - 4 and g(x) = 3x + 1, then what is the sum  [#permalink]

Show Tags

New post 09 Apr 2017, 02:05
Bunuel wrote:


If \(f(x) = 5x^2 - 4\) and \(g(x) = 3x + 1\), then what is the sum of all the values of \(m\) for which \(f(m - 1) = g(m^2 + 1)\) ?

A. -10
B. -5
C. 0
D. 5
E. 10

Kudos for a correct solution.



Pleas find attached the solution.

My opinion: it's highly unlikely to see a question based on these concepts in actual GMAT exam.

Posted from my mobile device
Attachments

File comment: GMATINSIGHT
1491728677848164508652.jpg
1491728677848164508652.jpg [ 2.91 MiB | Viewed 10429 times ]


_________________
Prosper!!!
GMATinsight
Bhoopendra Singh and Dr.Sushma Jha
e-mail: info@GMATinsight.com I Call us : +91-9999687183 / 9891333772
Online One-on-One Skype based classes and Classroom Coaching in South and West Delhi
http://www.GMATinsight.com/testimonials.html

ACCESS FREE GMAT TESTS HERE:22 ONLINE FREE (FULL LENGTH) GMAT CAT (PRACTICE TESTS) LINK COLLECTION
SVP
SVP
User avatar
V
Joined: 26 Mar 2013
Posts: 2345
Reviews Badge CAT Tests
Re: If f(x) = 5x^2 - 4 and g(x) = 3x + 1, then what is the sum  [#permalink]

Show Tags

New post 10 Apr 2017, 02:11
GMATinsight wrote:

Pleas find attached the solution.

My opinion: it's highly unlikely to see a question based on these concepts in actual GMAT exam.



Dear GMATInsight,

I'd like to draw you attention that there is an error in f(x) function. You have changed it from (-4) to (+4). The final quadratic equation should be:

2m^2 - 10m - 3 = 0
CEO
CEO
User avatar
D
Status: GMATINSIGHT Tutor
Joined: 08 Jul 2010
Posts: 2977
Location: India
GMAT: INSIGHT
Schools: Darden '21
WE: Education (Education)
Reviews Badge
Re: If f(x) = 5x^2 - 4 and g(x) = 3x + 1, then what is the sum  [#permalink]

Show Tags

New post 10 Apr 2017, 03:18
Mo2men wrote:
GMATinsight wrote:

Pleas find attached the solution.

My opinion: it's highly unlikely to see a question based on these concepts in actual GMAT exam.



Dear GMATInsight,

I'd like to draw you attention that there is an error in f(x) function. You have changed it from (-4) to (+4). The final quadratic equation should be:

2m^2 - 10m - 3 = 0


Thanks for notifying my mistake... However the pleasant surprise is that answer still doesn't change as the answer is dependent on the coefficients of x^2 and x...

So I hope that is ok if I accept the mistake made in first step however endorse the method to find answer (roots) of a quadratic equation. :)
_________________
Prosper!!!
GMATinsight
Bhoopendra Singh and Dr.Sushma Jha
e-mail: info@GMATinsight.com I Call us : +91-9999687183 / 9891333772
Online One-on-One Skype based classes and Classroom Coaching in South and West Delhi
http://www.GMATinsight.com/testimonials.html

ACCESS FREE GMAT TESTS HERE:22 ONLINE FREE (FULL LENGTH) GMAT CAT (PRACTICE TESTS) LINK COLLECTION
Non-Human User
User avatar
Joined: 09 Sep 2013
Posts: 13183
Re: If f(x) = 5x^2 - 4 and g(x) = 3x + 1, then what is the sum  [#permalink]

Show Tags

New post 05 Aug 2019, 20:05
Hello from the GMAT Club BumpBot!

Thanks to another GMAT Club member, I have just discovered this valuable topic, yet it had no discussion for over a year. I am now bumping it up - doing my job. I think you may find it valuable (esp those replies with Kudos).

Want to see all other topics I dig out? Follow me (click follow button on profile). You will receive a summary of all topics I bump in your profile area as well as via email.
_________________
GMAT Club Bot
Re: If f(x) = 5x^2 - 4 and g(x) = 3x + 1, then what is the sum   [#permalink] 05 Aug 2019, 20:05
Display posts from previous: Sort by

If f(x) = 5x^2 - 4 and g(x) = 3x + 1, then what is the sum

  new topic post reply Question banks Downloads My Bookmarks Reviews Important topics  





Powered by phpBB © phpBB Group | Emoji artwork provided by EmojiOne